Promising composites for wear resistant load-bearing implant applications: Low elastic moduli of β Ti–Nb alloy reinforced with TiC particles and/or TiB whiskers - Gonçalves, Vinícius Richieri Manso [UNESP]; Corrêa, Diego Rafael Nespeque [UNESP]; de Sousa, Tiago dos Santos Pereira [UNESP]; Pintão, Carlos Alberto Fonzar [UNESP]; Grandini, Carlos Roberto [UNESP]; Afonso, Conrado Ramos Moreira; Lisboa-Filho, Paulo Noronha [UNESP] (Elsevier, 2024)
Despite β-type Ti alloys achieving a low elastic modulus, metallic implants generally exhibit poor wear resistance. To address this issue, in-situ Ti-based matrix composites (TMCs) are considered due to their strong bonding at the matrix/reinforcement interface. While TiC particles and TiB whiskers are common reinforcements for in-situ TMCs, limited research combines their effects with the low elastic modulus of Ti alloys. Here, we present a novel approach using arc-melting on Ti–40Nb alloy with 5 vol% additions of NbC, NbB2, and B4C. Respectively, three TMCs were obtained with the β-type Ti–Nb matrices reinforced individually with TiC particles, TiB whiskers, and hybridized with both. The produced TMCs exhibited the same passive behavior of the unreinforced Ti–40Nb alloy. However, tribocorrosion resistances were improved, as TMCs achieved nobler potentials during sliding than the unreinforced alloy (−0.5 and −0.9 V, respectively). Notably, the TiB-reinforced and the hybrid reinforced TMCs displayed minimal wear damage, while the TiC-reinforced TMC achieved a remarkable low elastic modulus of approximately 73 GPa. This study introduces promising alternatives for wear-resistant load-bearing implant applications.
Keywords: Biomaterials; Composites; Micromechanics; Titanium alloys; Tribo-electrochemical behavior